Analisis Pendapatan UMKM Seblak Bandung Slowdown Sebelum Dan Sesudah Menggunakan Digital Payment Di Kabupaten Karawang - Sri Mulyani; Aji Tuhagana; Dwi Epty Hidayaty (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine MSME income before and after using digital payments. This research was conducted using a qualitative descriptive approach with a triangulation analysis method. The data used in this study is primary data obtained directly from the owner of the Bandung Slowdown seblak business through observation, interviews and documentation. while for secondary data obtained from books, journals, literacy studies, websites and other media. Based on the results of the study, it was shown that the slowdown of MSME income before using digital payments often faced challenges in terms of transaction efficiency and customer accessibility, this became an obstacle in increasing MSME income. The income of MSMEs in Seblak Bandung has slowdown after using digital payments to experience an increase. Because many consumers are already using digital payments, digital payments also speed up the payment process and reduce queuing time. This transaction speed creates opportunities for increased transaction volume and purchase frequency, which directly contributes to higher revenue. By using digital payment instruments, the Seblak Bandung Slowdown MSMEs have succeeded in overcoming the problems of transaction efficiency and customer accessibility. A faster and more accurate payment process reduces queue barriers and provides a more comfortable shopping experience for consumers. This drives increased transaction frequency, creates customer loyalty, and generates recommendations. so that these MSMEs are able to optimize their business growth in a competitive market. Keywords: income, digital payment, MSMEs